First-order selfadjoint singular differential operators in a hilbert space of vector functions - (:unkn) unknown (Texas State University - San Marcos, 2017)
In this article, we give a representation of all selfadjoint extensions of the minimal operator generated by first-order linear symmetric multipoint singular differential expression, with operator coefficient in the direct sum of Hilbert spaces of vector-functions defined at the semi-infinite intervals. To this end we use the Calkin-Gorbachuk method. Finally, the geometry of spectrum set of such extensions is researched. © 2017 Texas State University.
Keywords: Deficiency indeces; Multipoint singular differential expression; Spectrum; Symmetric and selfadjoint differential operator